Development of Video Tutorials for Making Learning Media Based on Augmented Reality on Ion Material - Qois Natasya; Hairida; Masriani; Rahmat Rasmawan; Eny Enawaty (Postgraduate, University of Mataram, 2025)
Ionic matter is an abstract material that is included in the submicroscopic level. Augmented reality is a media that can be used to overcome these problems. This research aims to identify the level of validity and show the response of educators and students to video tutorials on making augmented reality-based learning media on ion material. The level of product validity is based on the results of validation tests by experts, while the teacher's response is from the results of the teacher's response test questionnaire on chemistry and junior high school chemistry subjects. Student responses from chemistry education students at FKIP Tanjungpura University class of 2020. The method used is development using a design thinking approach. The research results show that the average percentage results in terms of media, material and language validity is 95.2%, so it can be categorized as very valid. Then, the teacher's response obtained an average percentage result of 89.9% and the student response was 88.85%. Thus, it is concluded that the resulting product received a very good response from educators and students.